Balanced Carrier Mobilities: Not a Necessary Condition for High‐Efficiency Thin Organic Solar Cells as Determined by MIS‐CELIV. Issue 4 (9th October 2013) - Armin, Ardalan; Juska, Gytis; Ullah, Mujeeb; Velusamy, Marappan; Burn, Paul L.; Meredith, Paul; Pivrikas, Almantas
<x xml:space="preserve">Abstract</x> A novel technique based upon injection‐charge extraction by linearly increasing voltage (i‐CELIV) in a metal‐insulator‐semiconductor (MIS) diode structure is described for studying charge transport in organic semiconductors. The technique (MIS‐CELIV) allows selective measurement of both electron and hole mobilities of organic solar cells with active layers thicknesses representative of operational devices. The method is used to study the model high efficiency bulk heterojunction combination poly[N‐9′′‐heptadecanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)] (PCDTBT) and [6, 6]‐phenyl C70‐butyric acid methyl ester (PC70BM) at various blend ratios. The absence of bipolar transport in PCDTBT‐and‐PC70BM‐only diodes is shown and strongly imbalanced carrier mobility is found in the most efficient "optimized" blend ratios. The mobility measurements are correlated with overall device performance and it is found that balanced and high charge carrier mobility are not necessarily required for high efficiencies in thin film organic solar cells.